The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1111/joim.12599
|View full text |Cite
|
Sign up to set email alerts
|

Acute caloric restriction counteracts hepatic bile acid and cholesterol deficiency in morbid obesity

Abstract: Abstract. Straniero S, Rosqvist F, Edholm D, Ahlstr€ om H, Kullberg J, Sundbom M, Ris erus U,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 50 publications
2
18
0
Order By: Relevance
“…In total, three studies assessed the association of fasting 7α‐hydroxy‐4‐cholesten‐3‐one (C4) with obesity, of which two showed higher C4 level associated with obesity 23,28 while the other study 42 had directionally similar estimates that were not statistically significant. However, meta‐analysis was not reported for C4 because one of the studies 28 had an extremely small variance, which contributed most of the weight to the estimate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, three studies assessed the association of fasting 7α‐hydroxy‐4‐cholesten‐3‐one (C4) with obesity, of which two showed higher C4 level associated with obesity 23,28 while the other study 42 had directionally similar estimates that were not statistically significant. However, meta‐analysis was not reported for C4 because one of the studies 28 had an extremely small variance, which contributed most of the weight to the estimate.…”
Section: Resultsmentioning
confidence: 99%
“…LCD does not appear to affect BA metabolism, as reflected by the consistently unchanged FGF19. Conversely, Straniero et al reported VLCD reduced BAs and C4 acutely, 23 suggesting inhibition of BA synthesis. Evidence is still limited, and the effect of LCD on BA remains unclear.…”
Section: Discussionmentioning
confidence: 95%
“…Although firm conclusions about causal relationships should not be purely based on observed correlations, the intestinal microbiota is thus a plausible candidate that may explain observed differences in bile acid levels across the diet groups. Another explanation for the lowered bile acid levels in the colonic luminal content of mice on CR is based on previous observations that faecal excretion of bile acids is reduced upon CR in obese individuals, which is presumably due to a lowered food mass in the colon [72] or due to more efficient uptake in the ileum [73]. In our study, levels of SCFAs in the colonic luminal content were relatively low, which could be inherent to our semi-synthetic diets low in dietary fibre as compared to regular chow diets.…”
Section: Discussionmentioning
confidence: 99%
“…Bile-acidactivated signaling pathways have become attractive therapeutic targets for metabolic disorders, such as obesity, type 2 diabetes, hypertriglyceridemia, and atherosclerosis, as well as other associated chronic diseases, such as nonalcoholic steatohepatitis [82,83]. The results have shown that a 40% CR increased the BA pool size (162%) and total BAs in gallbladder, small intestinal contents, and serum, with contributions mainly from taurocholic acid (TCA) and some secondary BAs, such as taurodeoxycholic acid, deoxycholic acid, lithocholic acid (LCA), w-muricholic acid, and hyodeoxycholic acid [84][85][86]. Increases in these CR-induced BAs might be due to an increase in the rate of BA synthesis, conjugation in liver and intracellular transport in the ileum.…”
Section: Bile Acidsmentioning
confidence: 99%